Perbandingan berat badan pada akseptor kontrasepsi hormonal oral kombinasi sebelum, sesudah 6 bulan dan 12 bulan penggunaan - Dewi Andriyati; Rusli P. Barus; Khairani Sukatendel; Muldjadi Affendy; Henry Salim Siregar; Johny Marpaung (Fakultas Kedokteran USU, 2014)
Background : Hormonal contraceptive is the most effective and reversible contraceptive method to prevent a pregnancy. Combined hormonal oral contraceptive primarily work by preventing ovulation. Ovulation was blocked by an action in hypothalamushypophyse-ovarium axys to reduce luteinizing hormone (LH) dan folicle-stimulating hormone (FSH). One of side effect of combined hormonal oral contraceptive pill use is increase the body weight, especially in the first year of use. Because of this side effect can lead to noncompliance or discontinuation of COCs, it takes knowledge of the patients about the side effects that can occur and how to prevent it.Methods : This study is observational analytic, which uses secondary data from medical records of family planning acceptors who use combined hormonal oral contraceptive pill for at least 12 months which is carried out in December 2014 - January 2015 in Public Health Center Helvetia Medan.Results : Mean value of maternal body weight before use of combined hormonal oral contraceptive pill is 57.35 kg, after 6 months of use is 58 kg, and after 12 months of use is 58.28 kg. Based on these results, with the paired t-test between maternal body weight before and after 6 months of use, it gets p value <0.05, which means there is a significant difference between body weight before and after 6 months use of combined hormonal oral contraceptive pill. In the paired t-test comparing the maternal body weight before and after 12 months of use, it gets p value <0.05, which showed a significant difference between body weight before and after 12 months use of combined hormonal oral contraceptive pill. And paired t-test comparing body weight after 6 months and 12 months of use, it gets p value <0.05, which means there is a significant difference between body weight after 6 months and after 12 months use of combined hormonal oral contraceptive pill.Conclusion : There is a significant maternal weight gain before, after 6 months and after 12 months use of combined hormonal oral contraceptive pill.Keywords : body weight, oral contraceptive, family planning